A study on condolence strategies by Jordanian students at Irbid University College - Yasser Al-Shboul (Universitas Syiah Kuala, 2022)
This study aimed to investigate the strategies of condolence speech act as expressed by Jordanian students at Irbid University College and identified the respective role of social power and social distance in offering these strategies. It employed qualitative and quantitative research methods, and the study participants included 100 university students ranging from 19 to 23 years old. The data were collected using an adapted version of the discourse completion test and coded based on the coding schema. The results of the study demonstrated that praying for God's mercy and forgiveness for the deceased was the most frequent strategy used by the participants, and expressing sympathy was the least frequently used strategy. When the power and distance aspects of the relationship between the speakers are concerned, the results showed that some of the strategies such as 'praying for God's mercy and forgiveness to be with the deceased' and 'offering condolences' are low-risk strategies to threaten the face needs of the bereaved people. Moreover, the results showed that the use of these strategies was mainly attributed to the participants' culture, religious orientation, social power, and social distance between the interlocutors. Finally, some pedagogical implications and suggestions for future research are briefly discussed in this article.